Play Therapy and Psychoeducational School-Based Group Interventions: A Comparison of Treatment Effectiveness. Issue 3 (3rd July 2018) - Swank, Jacqueline M.; Cheung, Christopher; Williams, Sydney A.
Abstract : This study focused on using a single case research design (SCRD) to compare the effectiveness of a child-centered group play therapy intervention to a psychoeducational group intervention (skillstreaming), and a group that received no intervention for 6 weeks. A group of 10 young children (kindergarten and Grade 1) were randomly assigned to 1 of the 3 groups. We found that children participating in the CCGPT intervention were 4.18 times more likely to have a decrease in total problem behavior across the 6-week period compared to children in the skillstreaming group, and 1.61 times more likely than children in the wait-list group.